Multidisciplinary approach of congenitally missing upper laterals: A case study - R Chandrasekar; K S Sridevi (Wolters Kluwer Medknow Publications, 2012)
In an orthodontic patient, missing teeth will require restoration or reshaping of an adjacent tooth, after the orthodontic treatment. Furthermore, each type of restoration may require slightly different tooth position. Therefore, it is mandatory for the team to establish a treatment plan. The orthodontist should join hands with the restorative dentist and consult before the treatment plan. However, some adult orthodontic patients may have several missing permanent teeth. If teeth have been absent for several years, the remaining teeth may have been drifted. In such situation, it may be necessary to position the teeth in unusual place. These patients may require a combination of orthodontic and restorative dentistry to rehabilitate their occlusion. In these patients, it may be difficult for the orthodontist to visualize or foresee the final result as she/he may not be aware of restorative requirements or the eventual restoration plans and vice versa for the restorative dentist also.